Angels and Demons: The Effect of Ethical Leadership on Machiavellian Employees’ Work Behaviors - Belschak, Frank D.; Den Hartog, Deanne N.; De Hoogh, Annebel H. B. (Frontiers in Psychology, 2018)
Machiavellians can be characterized as goal-driven people who are willing to use all possible means to achieve their ends, and employees scoring high on Machiavellianism are thus predisposed to engage in unethical and organizationally undesirable behaviors. We propose that leadership can help to manage such employees in a way that reduces undesirable and increases desirable behaviors. Studies on the effects of leadership styles on Machiavellian employees are scarce. Here we investigate the relationship of ethical leadership with prosocial (helping colleagues or affiliative OCB) and antisocial work behavior (knowledge hiding and emotional manipulation) for employees who are higher or lower in Machiavellianism. The effect of an ethical leadership style on employees predisposed to engage in unethical behaviors has not been investigated so far. In a cross-sectional multi-source survey study among a sample of 159 unique leader-follower dyads, we find interaction effects between leadership and employee Machiavellianism for prosocial and antisocial work behavior. As expected, employee Machiavellianism comes with reduced helping behavior and increased knowledge hiding and emotional manipulation, but only when ethical leadership is low. Under highly ethical leaders, such increases in organizationally undesirable behaviors of Machiavellian employees do not occur. While the cross-sectional design precludes conclusions about the direction of causality, findings of our study suggest to further explore (and from a practical perspective to invest in) ethical leadership as a potential remedy for undesirable behavior of Machiavellian employees.